Partitioning of chemical contaminants to microplastics: Sorption mechanisms, environmental distribution and effects on toxicity and bioaccumulation - Tourinho, Paula S; Kočí, Vladimír; Loureiro, Susana; van Gestel, Cornelis A M (Environmental pollution (1987), 2019)
There is an increasing awareness of the threats posed by the worldwide presence of microplastics (MPs) in the environment. Due to their high persistence, MPs will accumulate in the environment and their quantities tend to increase with time. MPs end up in environments where often also chemical contaminants are present. Since the early 2000s, the number of studies on the sorption of chemicals to plastic particles has exponentially increased. The objective of this study was to critically review the literature to identify the most important factors affecting the sorption of chemical contaminants to MPs. These factors include the physicochemical properties of both the MPs and the chemical contaminants as well as environmental characteristics. A limited number of studies on soil together with an increased notion of the importance of this compartment as a final sink for MPs was observed. Therefore, we assessed the distribution of model chemicals (two PCBs and phenanthrene) in the soil compartment in the presence of MPs using a mass balance model. The results showed a high variation among chemicals and microplastic types. Overall, a higher partitioning to MPs of chemical contaminants in soil is expected in comparison to aquatic environments. As sorption to a large extent determines bioavailability, the effects of combined exposure to chemicals and MPs on the toxicity and bioaccumulation in biota are discussed. Finally, some considerations regarding sorption and toxicity studies using MPs are given.
Keywords: chemické látky znečišťující vodu; Plastics; Environmental Monitoring; polychlorované bifenyly; monitorování životního prostředí; Models, Chemical; Polychlorinated Biphenyls; Water Pollutants, Chemical; společenstvo; Soil; Phenanthrenes; biologická dostupnost; lidé; Humans; Environmental Exposure; Biota; Biological Availability; plastické hmoty; půda; chemické modely; vystavení vlivu životního prostředí; fenantreny